Contemplating Stars and Solving Mysteries: Rationality in Mark Haddon's the Curious Incident of the Dog in the Nighttime. Issue 1 (16th June 2022) - Bissonette, Vincent
Abstract: The passage discussed in this essay comes from a moment in Mark Haddon's The Curious Incident of the Dog in the Night-Time when the protagonist-narrator Christopher's entire worldview is threatened. He has been trying to solve a mystery of who killed the neighbor's dog, and he has just learned that his father is the killer and that his mother, whom he thought dead (because that's what his father told him), is living in London with her lover. As Christopher looks at the stars, he explains to the reader why this is a good way to cope with "difficult things" in life. Through a close reading of the passage, I show how Christopher positions rationality in order to discuss disorder and violence, while insulating himself from it. I go on to argue that his use of the whodunit as his genre of choice serves a similar purpose. In both cases, however, the novel shows the limitations of rationality. It may be a helpful coping mechanism, but personal growth requires engaging in the emotional complexity and human messiness.